Relationship between Degree of Dependency and Hospitalization Time of Surgical Patients - Asenjo-Alarcón, José Ander; Vergara Cieza, Luz Elita (Investigación y Educación en Enfermería, 2023)
Objective. This work sought to establish the relationship between the degree of dependency with hospitalization time of patients intervened surgically in a regional hospital of Peru. Methods. The study was analytical, cross-sectional with retrospective data collection, studying 380 patients treated in the surgical service at Regional hospital Docente in the municipality of Cajamarca (Peru). The patients’ demographic and clinical information was obtained from the daily care records in the hospital’s surgery service. The univariate description was conducted through absolute and relative frequencies and confidence intervals for proportions at 95%; for the association between the degree of dependency and hospitalization time Log Rank (Mantel-Cox) – Chi-square was applied, as well as the Kaplan-Meier survival analysis, with statistical significance of p<0.05. Results. The study had 53.4% male patients, with mean age of 35.3 years, referrals from operating room (64.7%), surgery specialty (66.6%) and the most-frequent surgical intervention was appendectomy (49.7%). Mean hospitalization time was 10 days; 88.1% of the patients had grade-II dependency. The degree of patient dependency had a significant impact on the days of post-surgery hospitalization with direct relationship between both variables (p=0.038). Conclusion. Hospitalization time is determined by the degree of dependency of patients subjected to a surgical intervention; thereby, it is fundamental to anticipate all the necessary resources for proper care management.